Giant magnetoresistance effect in Co/Cu/Co nanostructures - Sakrani, Samsudi; Wahab, Yusof; Lau, Y. C. (Elsevier B.V., 2007)
The giant magnetoresistance effect (GMR) in Co/Cu/Co nanostructures is investigated in association with different sets of experimental conditions. GMR shows an up-down variation with increasing Co film thickness, with a peak for 6 nm thickness. A rather similar trend was observed in annealed samples with maximum annealing temperature of 400 Â°C. There is also a tendency of GMR to change with the number of Co/Cu bilayers and argon gas pressure introduced during the deposition, as indicated by the unstable wavy like curves.